Micropterygium longicellulatum (Lepidoziaceae, Marchantiophyta), a new species from Colombia - Uribe, Jaime; Linares, Edgar L. (Phytotaxa, 2015)
We describe a new leafy liverwort species, Micropterygium longicellulatum, collected on Cerro del Torrá, in San José del Palmar, southern Chocó, in the biogeographic Chocó region in Colombia. The new species is characterized by its radially symmetric stems; very long leaf cells, to 80 µm; and strongly concave leaves and underleaves.